2012
DOI: 10.1371/journal.pone.0032546
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Affinities of the Central Indian Tribal Populations

Abstract: BackgroundThe central Indian state Madhya Pradesh is often called as ‘heart of India’ and has always been an important region functioning as a trinexus belt for three major language families (Indo-European, Dravidian and Austroasiatic). There are less detailed genetic studies on the populations inhabited in this region. Therefore, this study is an attempt for extensive characterization of genetic ancestries of three tribal populations, namely; Bharia, Bhil and Sahariya, inhabiting this region using haploid and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 27 publications
1
30
2
Order By: Relevance
“…We present data in Table 1 (as well as in Fig 6) for the latitude and longitude of the locations of each tribe whose genetic composition with regard to contributions from the major ancestral groups have been provided by Sharma et al [48] and Basu et al [14]. The results of our simulations (Fig 4F) seem to offer suggest that the proportions of genetic contributions in various tribes should have a longitude dependence for roughly similar values of latitude.…”
Section: Resultssupporting
confidence: 55%
“…We present data in Table 1 (as well as in Fig 6) for the latitude and longitude of the locations of each tribe whose genetic composition with regard to contributions from the major ancestral groups have been provided by Sharma et al [48] and Basu et al [14]. The results of our simulations (Fig 4F) seem to offer suggest that the proportions of genetic contributions in various tribes should have a longitude dependence for roughly similar values of latitude.…”
Section: Resultssupporting
confidence: 55%
“…East Asian specific Haplogroup F1 was observed highest among all the studied populations (Table 1 and Table S1), and shared their closest haplotypes with Northeast Indian populations. In contrast to the high endogamy observed among other Indian populations [8][12], the massive haplogroup sharing among all the three populations suggest that the maternal boundaries in this region is highly permeable (Table 1). …”
Section: Resultsmentioning
confidence: 84%
“…To see the population structure and ancestry components among the studied population and surrounding groups, we have studied previously used 50 Ancestry Informative Markers (AIMs) [12], [20] and combined them with the same numbers of markers extracted from the literature [21], [22]. Four markers failed from the 99% quality control, therefore, we have used 46 AIMs for further analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies were reported at the context of disease epidemiology and genetics, upon various indian tribal communities, who are highly isolated both demographically and topogra phically, from the mainstream indian populations [4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%